Laudation in honour of professor dr. Jože Gasperič on the occasion of his 65th birthday - Jenko, Monika (Kovine zlitine tehnologije, 1997)
The background and the development of a well known scientist - dr. Jože Gasperič and the influence which his research work has in the field of vacuum science, development, construction and production of vacuum diffusion, human vacuum applications, over vacuum as vital component of the modern electronics.
Keywords: Gasperič, Jože, 1932-; biografije; 65 let